1993
DOI: 10.1213/00000539-199307000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fentanyl, Diazepam, and the Combination of Both on Arterial Baroreflex and Sympathetic Nerve Activity in Intact and Baro-Denervated Dogs

Abstract: The combination of fentanyl and diazepam significantly decreases systemic vascular resistance and blood pressure. We attempted to elucidate the reason the combination of these drugs can reduce blood pressure. In alpha-chloralose-anesthetized dogs, we investigated the effects of fentanyl and diazepam on mean arterial pressure (MAP) and arterial baroreflex control of renal sympathetic nerve activity (RSNA) in both intact (Study 1) and baroreflex-denervated dogs (Study 2). Study 1 included five dogs that received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 0 publications
4
19
0
1
Order By: Relevance
“…2,2s We reported that the effect of fentanyl on arterial baroreflex control of sympathetic nerve activity in dogs was negligible. 24 The current study also indicates this, since AHR/'ASBP was similar under the isoflurane-N20 anaesthesia with and without fentanyl before surgical stimulation (Figure 2). In the presence of surgical stimulation, however, fentanyl preserved heart rate baroreflex sensitivity ( Figure 2) and prevented an increase in ACTH (Figure 3), presumably by suppressing visceral surgical noxious stimuli during upper abdominal surgery.…”
Section: Discussionsupporting
confidence: 74%
“…2,2s We reported that the effect of fentanyl on arterial baroreflex control of sympathetic nerve activity in dogs was negligible. 24 The current study also indicates this, since AHR/'ASBP was similar under the isoflurane-N20 anaesthesia with and without fentanyl before surgical stimulation (Figure 2). In the presence of surgical stimulation, however, fentanyl preserved heart rate baroreflex sensitivity ( Figure 2) and prevented an increase in ACTH (Figure 3), presumably by suppressing visceral surgical noxious stimuli during upper abdominal surgery.…”
Section: Discussionsupporting
confidence: 74%
“…Several pharmaceuticals acting on GABA A receptors are known to influence blood pressure (Marty et al, 1986;Taneyama et al, 1993). This study suggests that a component of this effect could be mediated via tonic inhibition and consequently that tonic inhibition may be one target for CNS-mediated therapeutic actions on the cardiovascular system.…”
Section: Introductionmentioning
confidence: 62%
“…15,17,18 In anesthetized animals, opioid agonists generally decrease sympathetic activity. In anesthetized dogs and cats, fentanyl (5 to 50 g/kg IV) decreases splanchnic nerve activity and catecholamine plasma concentrations 3,4,6,7,9 and inhibits baroreflex responses. 38 In awake humans, however, the effects of opioid receptor agonists are less clear, because associated respiratory depression and/or an altered state of consciousness can hardly be controlled for.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…1,2 Acute administration of -opioid receptor agonists provides little insight in this respect, because any effects are blurred by respiratory depression, an altered state of consciousness, or even anesthesia. [3][4][5][6][7][8][9][10][11] Furthermore, under resting conditions, -opioid receptor blockade by naloxone, which attenuates the effects of endogenous opioids, does not change muscle sympathetic activity (MSA), arterial baroreflex gain, or catecholamine plasma concentrations in healthy volunteers. [12][13][14][15][16] Conversely, naloxone potentiates the increase in MSA during exercise and in response to lower-body negative pressure, indicating inhibition of MSA by endogenous opioids when the sympathetic nervous system is activated.…”
mentioning
confidence: 99%